2020
DOI: 10.3390/nu12020276
|View full text |Cite
|
Sign up to set email alerts
|

Lactate-Fortified Puerariae Radix Fermented by Bifidobacterium breve Improved Diet-Induced Metabolic Dysregulation via Alteration of Gut Microbial Communities

Abstract: Background: Puerariae Radix (PR), the dried root of Pueraria lobata, is reported to possess therapeutic efficacies against various diseases including obesity, diabetes, and hypertension. Fermentation-driven bioactivation of herbal medicines can result in improved therapeutic potencies and efficacies. Methods: C57BL/6J mice were fed a high-fat diet and fructose in water with PR (400 mg/kg) or PR fermented by Bifidobacterium breve (400 mg/kg) for 10 weeks. Histological staining, qPCR, Western blot, and 16s rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Several studies on animals suggest that the consumption of a high-fat diet (HFD) alters the gut microbial communities. Such an event may eventually manifest augmented intestinal permeability as a result of the gut barrier disintegration, leading ultimately to the development of metabolic endotoxemia, inflammation and metabolic disorders [ 10 , 11 , 12 , 13 ]. Therefore, controlling gut microbial composition may be a therapeutic strategy for the prevention and treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on animals suggest that the consumption of a high-fat diet (HFD) alters the gut microbial communities. Such an event may eventually manifest augmented intestinal permeability as a result of the gut barrier disintegration, leading ultimately to the development of metabolic endotoxemia, inflammation and metabolic disorders [ 10 , 11 , 12 , 13 ]. Therefore, controlling gut microbial composition may be a therapeutic strategy for the prevention and treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Lobata reduces the expression of inflammatory factors, such as TNF-α and IL-6. The expression levels of these inflammatory factors after Bifidobacterium fermentation when using P. Lobata were shown to be significantly lower than those in Pueraria without fermentation (22). Also, in the small intestine and colon of mice fed with a high-fat diet, puerarin, a functional extract of P. Lobata, was shown to block the expression of the proinflammatory factors IL-6 and monocyte chemoattractant protein-1 and increase the expression of the anti-inflammatory factor IL-10 (23).…”
Section: Pueraria Lobatamentioning
confidence: 84%
“…For PCR amplification, the following conditions were maintained: an initial denaturation step at 95 • C for 10 min followed by 40 cycles of amplification involving denaturation at 95 • C for 10 s, annealing at 55-58 • C for 5 s and extension at 72 • C for 10 s. The obtained PCR data were processed and analyzed using the dedicated Light Cycler software (version 1.2, Roche Applied Science) and normalized using glyceraldehyde-3-phosphatase dehydrogenase (GAPDH) as the housekeeping gene. The relative expression levels of the genes were measured, as described previously [16,19,26].…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Several animal studies reported that the consumption of a HFD modulates the gut microbial population. Such changes may enhance intestinal permeability due to gut-barrier disintegration, ultimately leading to the onset and development of metabolic endotoxemia, inflammation and metabolic disorders [16][17][18][19]. Therefore, regulating the gut microbial population via microbiome-based treatments, such as probiotics, prebiotics, fecal microbiota transplantation (FMT), metabolic surgery and drugs, may represent an effective targeted therapeutic strategy for the prevention and treatment of metabolic syndromes [12].…”
Section: Introductionmentioning
confidence: 99%